In-situ Hybridization for the Detection of Sacbrood Virus in Infected Larvae of the Honey Bee (Apis cerana). Issue 2 (February 2016) - Park, C.; Kang, H.S.; Jeong, J.; Kang, I.; Choi, K.; Yoo, M.-S.; Kim, Y.-H.; Kang, S.-W.; Lim, H.-Y.; Yoon, B.-S.; Chae, C.
Summary: The aim of this study was to develop and use in-situ hybridization (ISH) for the detection and localization of the sacbrood virus (SBV) in Korean honey bee ( Apis cerana ) larvae that were infected naturally with SBV. A 258 base pair cDNA probe for SBV was generated by polymerase chain reaction. Cells positive for viral genome typically showed a dark brown reaction in the cytoplasm. SBV was detected consistently in trophocytes and urocytes. The ISH was successfully applied to routinely fixed and processed tissues and thus should prove helpful in the diagnosis and characterization of viral distribution in infected larvae.